Chapter «Venerabilem preceptorem meum Boccaccium de Certaldo»: i rapporti (intertestuali) fra Giovanni Boccaccio erudito e Benvenuto da Imola - Tripodi, Giandomenico (Studi e saggi, 2022)
The text of the commentary to the Georgics of Benvenuto da Imola allows to illuminate the intertextual relationships between Benvenuto da Imola and Giovanni Boccaccio. Through a series of examples that highlight clear dependence on the Genealogia Deorum Gentilium, the De montibus and the Zibaldone membranaceo, the aim is to show Benvenuto's intellectual and cultural debt to the preceptor Boccaccio, thus configuring the Imolese as a personally known disciple and one of the first readers of Boccaccio's Latin erudite works.